THE ROLE OF CORONARY CIRCULATION RESTORATION AND CARDIOMYOCYTE METABOLISM OPTIMISATION IN THE MANAGEMENT OF HIGH-GRADE ISCHEMIC VENTRICULAR ARRHYTHMIA - T. V. Treshkur; A. A. Tatarinova; E. V. Parmon; D. V. Ryzhkova; E. V. Shlyakhto (Российский кардиологический журнал)
This study was aimed at the assessment of antiarrhythmic (AA) effectiveness of myocardial revascularisation (MR), as well as the evaluation of the Mexicor (M) role in the complex management of coronary heart disease (CHD) patients with high-grade ischemic ventricular arrhythmia (VA). In total, 34 patients underwent MR, based on the clinical, instrumental, and angiographic indications. Another 20 patients, who refused MR, or did not have clinical and angiographic indications for it, received conservative treatment, with an addition of M (300 mg/d). AA effectiveness of MR and M was assessed during Holter ECG monitoring, stress tests, and radionuclide examination. MR effectiveness, regardless of the intervention type, was maximal in the early post-surgery period (79,4%) and decreased later, reaching 55,8% after 12 months. In patients who did not undergo MR, M therapy demonstrated good AA effectiveness (75-100%). Therefore, the restoration of coronary circulation and myocardial metabolism agrees with the principles of complex etiopathogenetic treatment of ischemic VA.